2008
DOI: 10.1001/jama.299.17.2027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Folic Acid and B Vitamins on Risk of Cardiovascular Events and Total Mortality Among Women at High Risk for Cardiovascular Disease

Abstract: OMOCYSTEINE LEVELS HAVEbeen directly associated with cardiovascular risk in observational studies 1 ; and daily supplementation with folic acid, vitamin B 6 , vitamin B 12 , or a combination have been shown to reduce homocysteine levels to varying degrees in intervention studies. 2 Based on these data, several randomized trials were designed to test the hypothesis that supplementation with folic acid or B vitamins or both would prevent cardiovascular disease (CVD). However, published trials on patients with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
342
3
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 452 publications
(377 citation statements)
references
References 26 publications
(44 reference statements)
14
342
3
13
Order By: Relevance
“…The final fourteen RCT enrolled 39 420 patients. Among them, seven were included in the without folate fortification subgroup (28)(29)(30)(31)(32)(33)(34) , four were included in the with folate fortification subgroup (35)(36)(37)(38) and three were included in the partial folate fortification subgroup (39)(40)(41) . The screening process of potential articles is summarized in a flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The final fourteen RCT enrolled 39 420 patients. Among them, seven were included in the without folate fortification subgroup (28)(29)(30)(31)(32)(33)(34) , four were included in the with folate fortification subgroup (35)(36)(37)(38) and three were included in the partial folate fortification subgroup (39)(40)(41) . The screening process of potential articles is summarized in a flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…33 More importantly, if homocysteine is elevated in response to a betaine insufficiency, it will not be corrected by folic acid supplementation alone; and this could help to explain why folic acid therapies do not lead to the expected reduction in vascular events. 34 Therefore, the elevated homocysteine concentrations in these studies could be an indication of betaine insufficiency; and hence, using folic acid supplementation to lower plasma homocysteine concentrations would not lead to a sufficient decrease in plasma homocysteine to ultimately reduce the incidence of cardiovascular disease. It is important that future studies in this area control for both the betaine and folic acid intakes with respect to their influence on reducing the incidence of cardiovascular disease so that the effects of one can be carefully identified in relation to the other.…”
Section: Discussionmentioning
confidence: 97%
“…Several large, prospective trials have been conducted in recent years with the principal aim of studying the effects of lowering serum homocysteine concentrations with the use of B vitamins, including vitamin B 6 , on cardiovascular events (60,61) . Overall, the most compelling data from vitamin supplementation studies have demonstrated that vitamin B 6 is not effective for preventing the recurrence of cardiovascular events, including CAD, peripheral vascular disease and stroke (54,62,63) .…”
Section: Vitamin B 6 Supplementation Inflammation and Cvd Preventionmentioning
confidence: 99%